A Case of Psoriasis Vulgaris Treated with Brodalumab in a Hemodialysis Patient with End-Stage Renal Disease due to Diabetic Nephropathy - Masafumi Ishibashi; Rie Shiiyama (Hindawi Limited, 2020)
Psoriasis vulgaris is not frequently seen in patients on hemodialysis. However, these patients have limited treatment for psoriasis due to concerns about complications. We report the case of a psoriatic patient with end-stage renal disease on hemodialysis, safely treated with brodalumab. A 60-year-old man who presented with a 20-year history of recalcitrant severe psoriasis. He had diabetes from 40 years ago, and hemodialysis was initiated due to the progression of renal dysfunction two months ago. He was treated with brodalumab, and skin lesions improved markedly. He began to have a chronic cough four months after starting brodalumab. CT showed diffuse ground-glass shadow and pleural effusion in both lungs. Transbronchial lung biopsy showed no findings suggestive of interstitial pneumonia. In bronchoalveolar lavage fluid, mycobacteria and fungi were not identified. The T-SPOT.TB test was negative. It was considered to be a symptom of overflow due to excessive fluid volume based on insufficient dietary management. Brodalumab was continued, and respiratory symptoms improved with proper weight setting and adequate dietary control. No recurrence of rash has been seen 12 months after the initiation of brodalumab. There were no serious adverse events.